Docking-Guided 3D-QSAR Studies of 4-Aminoquinoline-1,3,5-triazines as Inhibitors for Plasmodium falciparum Dihydrofolate Reductase - Radite Yogaswara; Maria Ludya Pulung; Sri Hartati Yuliani; Enade Perdana Istyastono (Indonesian Journal of Chemistry, 2020)
Mutations in Plasmodium falciparum dihydrofolate reductase (PfDHFR), together with other mutations, hinder malaria elimination in Southeast Asia due to multiple drug resistance. In this article, molecular docking-guided three-dimensional (3D) quantitative structure-activity relationship (QSAR) analysis of 4-aminoquinoline-1,3,5-triazines as inhibitors for the wild-type (WT) PfDHFR to identify the molecular determinants of the inhibitors binding are presented. Compounds 4-aminoquinoline-1,3,5-triazines were reported promising to be developed as the non-resistant drugs. The 3D-QSAR analysis resulted in the best model with the R2 and Q2 values of 0.881 and 0.773, respectively. By correlating the molecular interaction fields (MIFs) of the best model to the docking pose employed to guide the 3D-QSAR analysis, S108 residue of the WT-PfDHFR was unfortunately recognized as one of the molecular determinants. Since the S108 residue is one of the mutation points of the PfDHFR mutants, the subsequent design strategy should modify the morpholine moiety to avoid the interaction with the S108 residue of the WT-PfDHFR.